2008
DOI: 10.1590/s1517-83822008000200031
|View full text |Cite
|
Sign up to set email alerts
|

Screening of lactic acid bacteria from vacuum packaged beef for antimicrobial activity

Abstract: The objective of this study was to isolate lactic acid bacteria (LAB) from vacuum packaged beef and to investigate their antagonist activity. LAB mean counts of 5.19 log cfu/cm 2 were obtained from five samples of vacuum packaged beef. Two hundred isolates were selected and screened for the inhibitory effect on five ATCC reference Lactobacillus strains. Thirty six isolates showed activity in the agar spot test against at least two of the indicator strains. However, only six cell free supernatants (CFS) from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 16 publications
2
25
0
Order By: Relevance
“…Similarly, Coconnier et al (1997) observed that the antimicrobial activity of supernatant of L. acidophilus strain LB from human was heat stable at 110 ο C for 1 and the activity was increased under acidic condition against S. Typhimurium, E. coli, Listeria monocytogenes, Shigella flexneri, Klebsiella pneumoniae, Pseudomonas aeruginosa and Enterobacter spp. Ollveira et al (2008) reported that L. acidophilus 30SC produced antimicrobial compound that was heat stable at 95°C for 20 minand 50% of activity was lost after heating at 121°C for 20 min Heating supernatant of L casei GC subgroup A isolated from vacuum packaged beef at 100 ο C for 10 min showed antagonistic activity against reference strains L. acidophilus, L. fermentum and L. plantarum (Oh et al, 2000). The antibacterial activity of strains of L. acidophilus 1 supernatants was active under acidic conditions between pH 3-5 against all target Gram negative bacteria (Table 7 and 8).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Coconnier et al (1997) observed that the antimicrobial activity of supernatant of L. acidophilus strain LB from human was heat stable at 110 ο C for 1 and the activity was increased under acidic condition against S. Typhimurium, E. coli, Listeria monocytogenes, Shigella flexneri, Klebsiella pneumoniae, Pseudomonas aeruginosa and Enterobacter spp. Ollveira et al (2008) reported that L. acidophilus 30SC produced antimicrobial compound that was heat stable at 95°C for 20 minand 50% of activity was lost after heating at 121°C for 20 min Heating supernatant of L casei GC subgroup A isolated from vacuum packaged beef at 100 ο C for 10 min showed antagonistic activity against reference strains L. acidophilus, L. fermentum and L. plantarum (Oh et al, 2000). The antibacterial activity of strains of L. acidophilus 1 supernatants was active under acidic conditions between pH 3-5 against all target Gram negative bacteria (Table 7 and 8).…”
Section: Discussionmentioning
confidence: 99%
“…Maurad and Meriem (2008) reported that the antimicrobial activity of L. plantarum isolated from camel milk butter was stable at pH 2-6 but the activity was lost at pH 8 against indicator strain of Lactococcus lactis B8. Ollveira et al (2008) isolated Lactobacillus casei GC subgroup A from vacuum packaged beef and had antagonistic activity against indicator strains of L. acidophilus, L. fermentum and L. plantarum; the activity was stable at pH 4-9.…”
Section: Discussionmentioning
confidence: 99%
“…Lactic acid bacteria (LAB) are GRAS (generally recognized as safe) microorganisms that modify the food enhancing quality, and additionally they possess nutritional and therapeutic benefits (20). The majority of the numerous reports on antimicrobial activity by LAB have focused on antibacterial effects (30), whereas there are only few reports on antifungal effects. The adaptability of LAB and yeasts to sourdoughs prepared from cereals, was investigated, the dominant LAB was Lactobacillus fermentum and S. cerevisiae constituted the dominating yeast (40).…”
Section: Introductionmentioning
confidence: 99%
“…Gram-negative bacteria (17). In this study, L. paracasei presented antagonistic activity against S. anginosus and G.…”
Section: Growth Curves Assaymentioning
confidence: 50%